A Planar Wideband Millimeter-Wave Antenna Array With Low Sidelobe Using '±1' Excitations - Dai, Xin; Li, Xun; Luk, Kwai-Man (IEEE transactions on antennas and propagation, 2021)
A new method is proposed to suppress the sidelobe level (SLL) of antenna array. Different from the conventional amplitude-tapered excitation method, '±1' excitations are used to feed the antenna array and achieve low SLL. The SLL is first optimized by using a modified binary particle swarm optimization algorithm with ideal '±1' excitations. Then, the ideal '±1' excitations are replaced with microstrip line feed and aperture-coupled magnetoelectric (ME) dipoles. The '+1' excited ME dipoles are fed from the default direction, while the '−1' excited ME dipoles are fed from the direction physically reversed. According to the optimized array configuration, combining the ME dipole elements with a 256-way parallel power divider, a planar 16×16 millimeter-wave antenna array is designed, fabricated, and measured. An overlapped working bandwidth of 38% (24.1-35.4 GHz) is obtained with an SWR less than 2.4 and SLL lower than −17.2 dB. The gain is up to 26.3 dBi. The new binary concept paves a new way for SLL suppressing.